A systematic review on selection and comparison of holistic agricultural sustainability assessment approaches - Naser Valizadeh; Dariush Hayati (Frontiers in Sustainable Food Systems)
General objective of this paper is to develop a methodological approach for comparing and selecting agricultural sustainability assessment frameworks introduced by scholars. Several sub-objectives have been considered, including “identifying and explaining holistic agricultural sustainability assessment frameworks,” “identifying and explaining comparison criteria of agricultural sustainability assessment frameworks,” “scoring agricultural sustainability assessment frameworks with respect to comparison criteria,” “evaluation of agricultural sustainability assessment frameworks with respect to comparison criteria,” and finally, “selection of the most appropriate framework.” The results of prioritization and comparison of the frameworks on the basis of comparison criteria using normalized scores and Analytical Hierarchical Process (AHP) demonstrate that, in general, Multi-Criteria Decision Analysis (MCDA) framework has a higher score than other frameworks. Although the present review shows that MCDA (2.144) has a higher overall score than other frameworks, it does not mean that this framework should be considered as one-size-fits-all framework in the field of agricultural sustainability assessment since other methods also have high scores in some (normative, systemic, and procedural) dimensions. For example, Farm-Level Indicators on New Topics (0.351), Sustainability Solution Space (0.351), and Sustainability Assessment of Farming and the Environment (0.267) frameworks have obtained high scores in systemic dimension. Similarly, Ecological Footprint Tool (0.699), Life Cycle Assessment Tool (0.684), and System Dynamic Simulation Tool (0.671) have obtained remarkable scores in the normative dimension, indicating the potential capacity of these frameworks in agricultural sustainability assessments.